Police discretion is a judgmental skill - Fadillah, Firman; Machyawaty, Tety; Sitorus, Tigor (Technium Social Sciences Journal, 2020)
This study aims to investigate the factors that influence the giving of discretion by police officers in the field in providing services to the public or when carrying out their functions and duties and responsibilities. Discretion is a phenomenon like Noumena. As a phenomenon, the empirical context of Discretion can be detected by the human senses. As a noumena, Discretion is in the context of the inner intentions and emotional conflicts of the discretion maker. Discretion is found in almost all aspects of human life, even doing an action or not doing an action can be categorized as Discretion. This Literature Study uses descriptive qualitative methods with results ; (1). Discretion tends to damage the normal structure of solving a problem, (2). Discretion is a method (mission) to make a balance between existing situations and conditions (reality) with expected situations and conditions (vision). (3). Discretionary actions relate to the interests of many parties, (4). Discretion must be carried out by the right person, in the right place, and at the right time.